The effect of time variation on the steels corrosion rate in 0.5 M H2SO4 solution - Afira Ainur Rosidah; Vuri Ayu Setyowati; Suheni Suheni; Rafly Rijayanto (Journal of Mechanical Engineering, Science, and Innovation, 2021)
Previous researches have carried out studying the corrosion behavior of steels, the most frequently used steels are medium carbon steel, alloy steel, and stainless steel. This is due to their wide range of applications. So, corrosion behavior is necessary to be analyzed for every steel type because of its wide function. This study was aimed to analyze the corrosion rate, macrostructure, and the XRD results of the AISI 1045, AISI 4140, and SS 304 which represent every steel type. Then, the steels were exposed to the 0.5M H2SO4 solution with various corrosion times. The variation of the corrosion time was 48, 96, and 144 hours. The results of this study revealed that AISI 1045 showed the highest corrosion rate with the value of 183.7 mpy at 144 hours of the time variation. All specimens obtained an increase in the corrosion rate with the increase in the corrosion time. Furthermore, for the macrostructure results, AISI 1045 and AISI 4140 gave obvious rust on the surface of the specimens for all time variation. The corrosion spots appear in the time variation of 96 and 144 hours for SS 304 specimens. XRD analysis confirmed the presence of metal oxides as corrosion products.